2022
DOI: 10.3389/fmicb.2022.1041314
|View full text |Cite
|
Sign up to set email alerts
|

In-depth systems biological evaluation of bovine alveolar macrophages suggests novel insights into molecular mechanisms underlying Mycobacterium bovis infection

Abstract: ObjectiveBovine tuberculosis (bTB) is a chronic respiratory infectious disease of domestic livestock caused by intracellular Mycobacterium bovis infection, which causes ~$3 billion in annual losses to global agriculture. Providing novel tools for bTB managements requires a comprehensive understanding of the molecular regulatory mechanisms underlying the M. bovis infection. Nevertheless, a combination of different bioinformatics and systems biology methods was used in this study in order to clearly understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 338 publications
(468 reference statements)
0
2
0
Order By: Relevance
“…In this study, signed weighted gene co-expression networks were constructed and then, 17 and 3 RNA-seq-based (including genes, TFs, and lncRNAs) and miRNA-seq-based (including miRNAs) modules were identified, respectively through the WGCNA approach. Technically, signed networks distinguish modules based on biological function with high accuracy and obtain more significant terms associated with co-expression patterns 32 . Then, module-trait relationships analysis of the WGCNA was performed between RNA-seq-based modules and clinical hallmarks of mastitis including SCC and TBC in order to extract significant highly-correlated RNA-seq-based modules with the aforementioned clinical measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, signed weighted gene co-expression networks were constructed and then, 17 and 3 RNA-seq-based (including genes, TFs, and lncRNAs) and miRNA-seq-based (including miRNAs) modules were identified, respectively through the WGCNA approach. Technically, signed networks distinguish modules based on biological function with high accuracy and obtain more significant terms associated with co-expression patterns 32 . Then, module-trait relationships analysis of the WGCNA was performed between RNA-seq-based modules and clinical hallmarks of mastitis including SCC and TBC in order to extract significant highly-correlated RNA-seq-based modules with the aforementioned clinical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Wang et al 31 identified 53 DE lncRNAs with inflammatory functions in bovine mammary epithelial cells using a high-throughput infection model of mastitis. However, existing research primarily focuses on individual RNA species (mRNAs, miRNAs, and lncRNAs) and fails to consider the effects of RNA clusters 32 .…”
Section: Introductionmentioning
confidence: 99%